T-2 toxin triggers depression-like behaviors via upregulation of dopamine transporter in nucleus accumbens of male mice - Zhigang Chen; Shaoyi Duan; Jialu Li; Jianming Su; Hongyu Lei (Ecotoxicology and Environmental Safety)
The T-2 toxin is a frequent contaminant in the global environment and agricultural production. Existing evidence suggests that the ingested T-2 toxin can enter the brain and exhibit neurotoxicity. However, it is still unknown whether T-2 toxin causes the depression-like behaviors. In this study, the mice were orally administrated with 1.5 mg/kg T-2 toxin daily for 14 d, and the depression-like behaviors were assessed by the tail suspension test (TST) and sucrose preference test (SPT). Here, the results showed that T-2 toxin exposure induced depression-like behaviors, manifested as behavioral despair and anhedonia, without anxiety-like behaviors. In addition, the reduced dopamine (DA) level and elevated dopamine transporter (DAT) level were found in reward center nucleus accumbens (NAc) receiving DAergic projection from ventral tegmental area (VTA) in brain after T-2 toxin administration, while there was no significant alteration in DA synthesis-related tyrosine hydroxylase (TH) and aromatic L-amino acid decarboxylase (AADC) in VTA and DA storage-related vesicle monoamine transporter 2 (VMAT2) in NAc. The local administration of DAT inhibitor AHN 1–055 hydrochloride into NAc alleviated T-2 toxin caused the depression-like behaviors. Importantly, the chemogenetic activation of the VTADA-NAc circuit increased the DA content in NAc and reversed the T-2 toxin-produced behavioral despair and anhedonia. Thus, our study for the first time illustrates DA dysregulation by upregulated DAT in NAc mediates T-2 toxin-triggered depression-like symptoms in mice. Meanwhile, this study establishes a novel causal relation between the neurotoxicant T-2 toxin exposure and the etiology of depression-like behaviors, and provides reference for the prevention and treatment for mycotoxin-induced depression-like symptoms.